Survey data on perceived sustainability and revisit intention of tourists to community-based tourismMendeley Data - Kien Trung Dao; Dat Dinh Nguyen; Duy Van Nguyen; Dat Ngoc Nguyen; Huong Thi Lan Pham (Data in Brief)
Tourism in mountainous provinces is attracting everyone in Vietnam. This kind of tourism is becoming popular in this country. Additionally, Sustainable tourism is increasingly of interest to tourists as well as organizations. The purpose of this study is to examine how tourists' perception of sustainability impacts their perception of and intentions to revisit community-based tourism destinations. The authors collected data on tourists' perceived sustainability and intentions to revisit community-based tourism sites. The survey data was collected from 295 tourists visiting community-based tourism destinations in mountainous provinces of Vietnam. We assessed the reliability using Confirmatory Factor Analysis (CFA) and discriminant validity using the AMOS software. The data will contribute insights into the research area of perceived sustainability and revisit intentions at community-based tourism destinations. Besides, the role of destination image, perceived value, and satisfaction are considered in this study.